2010
DOI: 10.1007/s11095-010-0089-7
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin: A Promising Molecule for Cancer Prevention

Abstract: Apigenin, a naturally occurring plant flavone, abundantly present in common fruits and vegetables is recognized as a bioactive flavonoid shown to possess anti-inflammatory, antioxidant and anticancer properties. Epidemiologic studies suggest that a diet rich in flavones is related to a decreased risk of certain cancers, particularly cancers of the breast, digestive tract, skin, prostate and certain hematological malignancies. It has been suggested that apigenin may be protective in other diseases that are affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
450
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 685 publications
(469 citation statements)
references
References 135 publications
7
450
0
12
Order By: Relevance
“…However, a number of other candidates emerged from the screen that warranted further investigation. Among these candidates was apigenin (4′,5,7,-trihydroxyflavone; MW, 270.24), a naturally occurring flavonoid present in several plants and having little or no toxicity when obtained from the diet (Ross andKasum 2002, Shukla andGupta 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of other candidates emerged from the screen that warranted further investigation. Among these candidates was apigenin (4′,5,7,-trihydroxyflavone; MW, 270.24), a naturally occurring flavonoid present in several plants and having little or no toxicity when obtained from the diet (Ross andKasum 2002, Shukla andGupta 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are a group of polyphenols that share similar chemical features and are abundant in vegetables, fruits and tea, amongst other products (2). Humans absorb a large amount of flavonoids orally, and epidemiological studies have revealed that the risk of certain types of cancer, particularly cancers of the breast, digestive tract, skin, prostate and certain hematological malignancies, is inversely correlated with intake of flavonoids (3,4). Flavonoids possess antioxidative, anti-inflammatory and antitumor properties (5).…”
Section: Introductionmentioning
confidence: 99%
“…Apigenin (4' ,5,7-trihydroxyflavone) is a promising chemopreventive agent that is abundantly present in fruits, vegetables, and teas (3). This compound has anticarcinogenic properties via diverse mechanisms and is suggested to have a tumor preventative effect (3,9).…”
Section: Introductionmentioning
confidence: 99%
“…For example, 2015 research found apigenin to inhibit the growth of breast cancer cells, including HER2-positive ones [24]. 2006 research published in Molecular Cancer found that apigenin inhibits growth of pancreatic cancer cells through suppression of cyclin B-associated cdc2 activity and G2/M cell cycle arrest [25].…”
Section: Parsleymentioning
confidence: 99%